Individuation process of time traveller in Time Machine (2018) novel - Delia Nur Amni; Mardliya Pratiwi Zamruddin (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
Personality is a trait or behavior included as the pattern of humans’ way of adapting themselves to their surroundings and shaped by the individuation process. This process is often reflected in character development in any literature within any genre, especially science fiction. Science fiction with a unique setting and metaphorical depiction influences the personality-building of the character, therefore becoming a potential for psychology-related analysis. This research applied individuation theory by Jung to analyze the character of the Time Traveller’s character in the Time Machine (2018) novel. The individuation process is the process of integrating consciousness and the unconscious aspects by passing five stages, involving four main archetypes, such as the persona, shadow, anima, and self. Time Traveller’s experience in time-traveling becomes a trigger of his individuation process. This research applied a descriptive qualitative analysis with a psychological approach to analyze the Time Traveller character. The result of this research is Time Traveller passed five stages, such as confront the unconscious, dethrone the persona, accepting the dark sides or shadow, accepting the anima, and transcend with involvement in his four main archetypes in each stage. The five stages that he faced were triggered by certain events and conflicts in the future world that slowly influenced his traits or behavior. In the end, Time Traveller’s personality made some better individual changes from ego-driven to empathetic with balanced emotions after his time-travelling. His time-traveling experience is considered not only a physical journey but also a metaphorical journey for the Time Traveller toward the wholeness of himself.